ANALISIS STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENJUALAN PADA USAHA BUKO PANDAN - Inne Syaidatun Nisa; Bella Aurelia Zerlina; Anggun Artanti; Dian Hakip Nurdiansyah (Jurnal Bina Bangsa Ekonomika, 2024)
This article research was made with the aim of knowing what marketing strategies are used by buko pandan business actors in increasing sales. In this study using qualitative descriptive approach method. The types and sources of data in writing this article are taken from primary data and secondary data. The analysis method used is descriptive analysis, where the marketing strategy refers to the concept of marketing mix and uses SWOT analysis (Strenght, Weakness, Opportunities, Threats). From the results of this study, it can be seen how the implementation of marketing mix marketing strategies and SWOT method analysis in an effort to increase sales of buko pandanus